Comparison of biomechanical properties of different implant-abutment connections - Kalpana Devaraju; Sanjana J Rao; Joel Koshy Joseph; Sampath Raju Kumara Kurapati (Wolters Kluwer Medknow Publications, 2018)
Implant abutment connection has proven to have a significant impact on the success of the prosthetic rehabilitation for an implant-supported restoration. This connection not only provides the base on which the restoration is supported but also maintains the integrity of the hard and the soft tissues surrounding the implant. In this review, we describe the performances of different implant-abutment connections that are the external implant connections, internal implant connections, and the Morse taper connections in terms of their mechanical properties, biological properties, and its biomechanical effects.